Options for Developing Countries to Deal with Global Food Commodity Market Volatility - Alexandros Sarris (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
The paper first reviews several issues relevant to global food commodity market volatility as it pertains to food security, and food importing developing countries, and then discusses international and national policies and measures to prevent or manage this volatility and related risks. It is shown that market volatility relates to unpredictability of market fundamentals, and price spikes occur when unpredictability increases excessively. The behavior of commodity prices and market volatility is reviewed and it is concluded that the exact modeling of these is difficult, making predictions of market volatility uncertain. The risks faced by food import developing countries are discussed and it is highlighted that the major risks involve not only large and unpredictable price variations but also trade finance as well as import contract enforcement. The problem of identifying a price spike is analyzed and it is seen that, despite difficulties in commodity modeling, there are empirical techniques that allow the assessment of the probabilities of price spikes, and could facilitate the triggering of responses. There appear to be few cost effective ways to prevent market upheavals, but there seem to be some ways, reviewed in the paper, to instill more confidence in markets and hence reduce the chances of such abnormal events. Most effective appear to be ways to actively manage food market volatility and risks of excessive price spikes. A range of appropriate market and non-market based measures are reviewed and some new ideas are offered in this context.
Keywords: 330